The diagnostic and therapeutic challenge of atrial flutter in children: a case report - Angelica De Nigris; Mattia Arenella; Giangiacomo Di Nardo; Giovanni Maria Di Marco; Annunziata Mormile; Daria Lauretta; Caterina De Simone; Angela Pepe; Rosaria Cosimi; Rossella Vastarella; Antonietta Giannattasio; Giovanni Salomone; et al. (BMC, 2023)
Abstract Background Palpitations represent a common cause for consultation in the pediatric Emergency Department (ED). Unlike adults, palpitations in children are less frequently dependent from the heart, recognizing other causes. Case presentation A 11-year-old male came to our pediatric ED for epigastric pain, vomiting and palpitations. During the previous 6 month the patient was affected by SARS-CoV-2 (Severe Acute Respiratory Syndrome Coronavirus). Electrocardiogram (ECG) revealed supraventricular tachycardia. Therefore, adenosine was administered unsuccessfully. The administration of adenosine, however, allowed us to make diagnosis of atypical atrial flutter. Multiple attempts at both electrical cardioversion, transesophageal atrial overdrive, and drug monotherapy were unsuccessful in our patient. Consequently, a triple therapy with amiodarone, flecainide, and beta-blocker was gradually designed to control the arrhythmic pattern with the restoration of a left upper atrial rhythm. There was not any evidence of sinus rhythm in the patient clinical history. Conclusions The present study underlines the rarity of this type of dysrhythmia in childhood and the difficulties in diagnosis and management, above all in a patient who has never showed sinus rhythm. Raising awareness of all available treatment options is essential for a better management of dysrhythmia in children